Analysis of the equilibrium process of flavor components during the aging period of Te-flavor Baijiu base liquor - ZHU Yunfei, LIN Pei, WU Shengwen, XIE Fangqian, ZENG Tingting, CAI Shan (Zhongguo niangzao)
Using new base liquor of Te-flavor Baijiu aged in 40 pottery jars as the research object, they were tested every 3 months and followed up for 2 years. Based on Pearson correlation analysis, the mutual equilibrium process of 6 flavor components of base liquor, including total acid/total ester, lactic acid/ethyl lactate, acetic acid/ethyl acetate, hexanoic acid/ethyl hexanoate, butyric acid/ethyl butyrate, and acetaldehyde/acetal during the aging period was analyzed from the perspective of chemical reaction equilibrium. Simultaneously, the effect of equilibrium on the sensory flavor of base liquor was analyzed by preparing simulated Baijiu samples before and after equilibrium. The results showed that acid-ester ratios of the new liquor were diverse, but these differences gradually decreased during the storage. The linear correlation coefficient R2 between acid and corresponding ethyl ester increased continuously, and the correlation coefficient (R2) reached more than 0.9 after 2 years aging. The acid-ester ratio was close to the same value, and the chemical reaction equilibrium was reached. It was found that there was a highly significant positive correlation between the reduction of Baijiu esterification concentration and the new liquor concentration after 2 years of storage (P<0.01), indicating that the greater the difference between the acid ester ratio and the equilibrium ratio of new liquor, the faster the equilibrium rate. Acetaldehyde and acetal increased synchronously during the aging process, and always maintained a good linear relationship. The chemical balance of flavor components could improve the aroma, sweetness, mellow and smoothness of the liquor. The main flavor components of Te-flavor Baijiu base liquor could be balanced when aged in pottery for 2 years.